The Impact of a Didactic Strategy using Technology to Strengthen the Learning of Mathematics - Navarro-Ibarra, Lizzeth; Cuevas-Salazar, Omar (Journal of Education and e-Learning Research, 2021)
The didactic strategy of this study consisted of the implementation of virtual practices for learning Mathematics at the university level. The objectives established to evaluate the impact of the strategy were to determine the contribution of these virtual practices and identify their effect on students’ academic performance. The strategy was carried out in the course Fundamentals of Mathematics, for first semester students in the Engineering programs at the Sonora Institute of Technology and 1,144 students participated between August 2018 and May 2019. The results proved that the students who participated scored higher in the course than those who did not participate. A dependency ratio was also found between the variables of students’ final grades in Fundamentals of Mathematics and the number of virtual practices they had carried out. The conclusion is that the didactic strategy significantly improves the passing rate and academic performance in the subject of Mathematics for which it was implemented.